Pengaruh Leverage dan Rasio Aktivitas terhadap Profitabilitas PT ABC Indonesia Tbk Periode 2014-2025 - Fifi Maharani; Achmad Ludvy (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effect of leverage measured by Debt to Asset Ratio (DAR) and activity ratio measured by Total Asset Turnover (TATO) on profitability measured by Return On Assets (ROA) at PT ABC Indonesia Tbk for the 2015–2024 period. The analysis is carried out both partially and simultaneously to provide an overview of the factors that affect the company's profitability. The type of research used is descriptive quantitative with secondary data obtained from the company's annual financial statements, in the form of balance sheet and income statements. Data analysis methods include t-test, f-test, and determination coefficient (R²). The results of the study show that partially, the Debt to Asset Ratio (DAR) does not have a significant effect on the Return On Assets (ROA). This indicates that the company's leverage level, in the form of a comparison of total debt to total assets, did not directly contribute to the level of profitability during the study period. Similarly, Total Asset Turnover (TATO) is also partially unaffected by ROA. These findings suggest that the effectiveness of a company in utilizing total assets to generate sales has not fully affected profitability. However, the results of the simultaneous test (F test) showed that DAR and TATO together had a significant effect on ROA. A determination coefficient value (R²) of 0.6037 or 60.37% indicates that the variation in the company's profitability can be explained by these two independent variables. Meanwhile, the remaining 39.63% was influenced by other factors outside the research model, such as operational efficiency, cost structure, marketing strategy, and external conditions of the retail industry. Thus, this study confirms the importance of comprehensively considering leverage and asset activity in managing a company's profitability, although the partial influence of each variable has not shown strong significance.